Liposclerosing Myxofibrous Tumor of the Cranial Vault: A Case Report. Issue 3 (12th March 2018) - Ploof, Jillian; Shaikh, Hamza; Melli, Jenny; Jour, George; Turtz, Alan
Abstract: BACKGROUND AND IMPORTANCE: Liposclerosing myxofibrous tumors (LSMFTs) are rare benign fibro-osseous tumors most frequently occurring in the proximal femur. We report the first case of this rare tumor occurring within the calvarium. CLINICAL PRESENTATION: Our patient presented with a 2-yr history of enlarging, painless, fixed mass over the left forehead. She underwent surgical resection and the mass was histologically confirmed to be a LSMFT. CONCLUSION: LSMFT is a rare tumor that should remain on the differential for lesions of the calvarium. When diagnosed, this lesion can be removed with the goal of gross total resection and excellent cosmesis can be achieved.